Factors Influencing the Occurrence of Chronic Energy Deficiency in High-Risk Pregnant Women - Eka Wira Adesty, Riana; Anggadita, Tania; Damayanti, Rini; Tunggal Mutika, Winnie (Faculty of Public Health Mulawarman University, Indonesia, 2025)
Background : Pregnant women suffering from CED are at risk of sudden maternal death in the perinatal period or at risk of giving birth to a low birth weight (LBW) baby (Pamangin, 2024) Objective : To find out the factors that influence the occurrence of chronic energy deficiency in pregnant women Research Methods/ Implementation Methods : A literature review using two databases namely Google Scholar and Garuda with keywords